PENGARUH HUTANG JATUH TEMPO TERHADAP KONSERVATISME AKUNTANSI - Karin Nimas Sita Riduwan; Suwarno Suwarno (PROCEEDING UMSURABAYA, 2022)
This research aims to determine the effect of maturing debt by adding control variables, namely, leverage, size, profitability on accounting conservatism. Samples were taken using a purposive sampling technique totaling 92 companies in non-financial companies listed on the Indonesia Stock Exchange in 2019. The data analysis techniques used were descriptive statistics, classical assumption tests, and multiple linear regression analysis. The results showed that the independent variable short term debt maturity, leverage and size control variable, had no effect on accounting conservatism. Based on the results of the interpretation of the independent variables in this study, it is hoped that researchers can add the Long Term Debt Maturity variable as a comparison with the Short Term Debt Maturity variable in the hope of proving more accurate research and producing data significance. While the control ROA have an effect on accounting conservatism.Keywords:Short Term Debt Maturity; Leverage; Size; ROA; Accounting Conservatism.Â